(untitled) (Research, Society and Development, 2021)
The Coronavirus disease 2019 (Covid-19) pandemic has become emergent and central to communications on social media, in which several perspectives and conceptions intertwine and oppose, sometimes creating rumors and fake news. The message flow of social media can be studied within the theoretical framework of social representations. For this purpose, 300 messages about Covid-19 were gathered: 100 of individual profiles, 100 of governments and 100 fake news. An analysis of thematic content has been conducted on the three corpora. Divergently from the other means of communication, it may be observed that the fake news results are about the Chinese origin of the virus, offer homemade advice for prevention and cure of the virus and are prone to contest social isolation. Messages from individual and governmental profiles are mostly not about the origin of the virus but provide advice on hygiene practices, garbage disposal, physical activities, psychological care and defend social isolation.